Importance of QD Purification Procedure on Surface Adsorbance of QDs and Performance of QD Sensitized Photoanodes - King, Laurie A; Riley, D. Jason (Journal of physical chemistry. C, 2012)
Quantum dots (QDs) have been utilized as light harvesting assemblies on photoanodes for applications in quantum dot sensitized solar cells. QDs are bound (sensitized) to a titanium dioxide surface using the bifunctional linker molecule 3-mercaptopropionic acid. The cadmium selenide QDs are synthesized following a trioctylphosphine oxide (TOPO) stabilized hot injection method. Prior to sensitization, QDs are subject to a common purification; cycles of alternate precipitation/redispersion in a nonsolvent/solvent. Through a systematic study, the critical role of this purification has been determined. With enhanced purification, the surface bound QD concentration has been shown to increase 5-fold. Imaging reveals that the QD agglomerates decrease in size and increase in population. Photocurrent measurements demonstrate the importance of the morphology and QD population on the ability of QD photoinjection and thus the necessity to control QD purification. These findings are discussed in light of recent literature on QD surface bound ligands.